Integrating Symptoms Into the Middle-Range Theory of Self-Care of Chronic Illness. (July 2019) - Riegel, Barbara; Jaarsma, Tiny; Lee, Christopher S.; Strömberg, Anna
Abstract : The Middle-Range Theory of Self-Care of Chronic Illness has been used widely since it was first published in 2012. With the goal of theoretical refinement in mind, we evaluated the theory to identify areas where the theory lacked clarity and could be improved. The concept of self-care monitoring was determined to be underdeveloped. We do not yet know how the process of symptom monitoring influences the symptom appraisal process. Also, the manner in which self-care monitoring and self-care management are associated was thought to need refinement. As both of these issues relate to symptoms, we decided to enrich the Middle-Range Theory with knowledge from theories about symptoms. Here, we propose a revision to the Middle-Range Theory of Self-Care of Chronic Illness where symptoms are clearly integrated with the self-care behaviors of self-care maintenance, monitoring, and management.